Prosedur Pengerjaan pada Sistem Digital BRIMEN pada PT BRI (Persero) Tbk. Kantor Wilayah Medan - Mutiara Amanda; Ditta Arsyilviasari; Syilviani Syilviani; Fetrisia Siregar; Fibri Rakhmawati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
The use of BRIMEN (BRI Document Management System) in digital document processing operations during internship activities at the Medan Regional Office of PT Bank Rakyat Indonesia (Persero) Tbk. is the main focus of this article. The objective of this study is to understand how the BRIMEN system contributes to the storage, retrieval, and classification of documents, particularly in relation to credit document management. This system was introduced to address common issues found in manual archiving, such as limited storage space, difficulties in document retrieval, and the risk of errors in preserving clients’ physical records. The research employed a descriptive qualitative approach through direct observation and active participation in daily workflows. The findings indicate that BRIMEN significantly improves operational efficiency by providing a more systematic and secure digitalization procedure for banking documents. The system not only reduces the risk of loss or damage to physical archives but also accelerates the process of data retrieval when required by work units. Through its classification and tracking features, BRIMEN ensures better consistency between digital data and physical documents, although several technical challenges remain, such as restricted access to storage rooms and difficulties in scanning older or non-standard documents. Overall, the results highlight the importance of implementing a well-structured digital document management system to support the smooth operation of modern banking institutions. BRIMEN represents a tangible step in BRI’s digital transformation, strengthening data security while simultaneously improving the quality of credit services delivered to customers. With continuous improvement, this system has the potential to serve as a model for digital document management that can be more widely adopted across Indonesia’s banking sector.